Exploring cause and explanation : historical ecology, demography, and movement in the American Southwest - Ramenofsky, Ann F. (Ann Felice), 1942-; Herhahn, Cynthia (Proceedings of the Southwest Symposium., 2016)
"The authors bring together three distinct archaeological themes--historical ecology, demography, and movement--and illustrates how the epistemological issues of cause and explanation link all three major themes into a coherent whole"--Provided by publisher